FAKTOR – FAKTOR YANG MEMPENGARUHI PERILAKU ORANGTUA DALAM MEMBERIKAN PENDIDIKAN SEKS USIA DINI PADA ANAK PRA SEKOLAH DI KOTA SEMARANG - Karin Gandeswari; Besar Tirto Husodo; Zahroh Shaluhiyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Sex education is one of the efforts that able to prevent children becoming victims of sexual violence. Semarang is the region with the highest rates of violence against women and children in Central Java in 2018. There are still many parents who do not take precautions by providing sex education to their children as early as possible so this can make children vulnerable to sexual violence. This study aims to analyze the factors that influence parental behavior in providing early sex education in pre-school children. The method used quantitative with cross sectional approach. The population in this study were parents' students in TK Labschool Unnes and PAUD Anak Bangsa 3 as many as 66 people through total sampling. This study uses univariate and bivariate analysis using chi square test. The results showed that 46 out of 66 parents (69.7%) had good behavior in providing early sex education to pre-school children. Educational factors (p - value = 0.004), employment (p - value = 0.048), exposure to information on sexual violence (p - value = 0.003), access to information (p - value = 0.038), knowledge (p - value = 0.005), attitudes (p - value = 0.015), family subjective norms (p - value = 0.015) and perceptions of behavioral control (p - value = 0.002) related to parental behavior in providing early sex education in pre-school children. Parents are expected to be able to improve their knowledge and skills regarding early sex education in children, especially regarding material constraints, ways of delivery for children regarding sex education